Analysis of validity, practicality, and readability of islamic STEAM activity storybook for early childhood - Azis, Yahya; Metafisika, Kartika; Ayu Lestari, Frida Anggraeni; Asistiana, Lisa (Universitas Islam Negeri Raden Intan Lampung, 2022)
So far, separating science and religion has brought the world into chaos. In contrast, science and religion do not need to be a dichotomy because they can be integrated constructively to solve problems in human life. This study aims to analyze the validity, practicality, and readability of Islamic Science, Technology, Engineering, Art, and Mathematics (STEAM) Activities for Early Childhood (AUD), which is part of design research. The research approach uses quantitative methods with a design that refers to the Plomp model. The results of the validity test show that the resulting product is very valid with improvements in standard and non-standard language, use of fonts, enlargement of font sizes, and improvements in Higher Order Thinking Skills (HOTS) questions. After going through the improvement of the prototype, readability, and practicality tests, the results were very good and suitable for use. The results and steps of this study can be used as a reference for other researchers who want to test the validity, practicality, and readability of reading product development for early childhood. In this STEAM Storybook product, more emphasis is placed on integrating Islamic content and activities with the Engineering Design Process.